2013
DOI: 10.1093/mnras/stt1149
|View full text |Cite
|
Sign up to set email alerts
|

Herschel-SPIRE Fourier transform spectroscopy of the nearby spiral galaxy IC 342★

Abstract: We present observations of the nearby spiral galaxy IC342 with the Herschel Spectral and Photometric Imaging Receiver (SPIRE) Fourier Transform Spectrometer. The spectral range afforded by SPIRE, 196-671 µm, allows us to access a number of 12 CO lines from J=4-3 to J=13-12 with the highest J transitions observed for the first time. In addition we present measurements of 13 CO, [CI] and [NII]. We use a radiative transfer code coupled with Bayesian likelihood analysis to model and constrain the temperature, dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 51 publications
6
47
0
Order By: Relevance
“…We tried to fit CO ladders in the central 45 with a single LVG component first, however, it does not produce a good fit. This is not surprising since the modeling results in previous studies (e.g., Kamenetzky et al 2012;Hailey-Dunsheath et al 2012;Rigopoulou et al 2013) have shown that the coexistence of multiple excitation gas components in nearby galaxies (also see Lu et al 2014). Therefore, we use two LVG components to model the gas excitation in the central 45 region.…”
Section: Two-component Modeling In the Central 45 Regionmentioning
confidence: 58%
“…We tried to fit CO ladders in the central 45 with a single LVG component first, however, it does not produce a good fit. This is not surprising since the modeling results in previous studies (e.g., Kamenetzky et al 2012;Hailey-Dunsheath et al 2012;Rigopoulou et al 2013) have shown that the coexistence of multiple excitation gas components in nearby galaxies (also see Lu et al 2014). Therefore, we use two LVG components to model the gas excitation in the central 45 region.…”
Section: Two-component Modeling In the Central 45 Regionmentioning
confidence: 58%
“…We determined the aperture correction of the Herschel CO[5-4] measurements using the IRAS imaging. In addition, we used data for the local spiral IC 342 from Rigopoulou et al (2013) and the MW.…”
Section: Comparison Samples Of Local Spirals and (U)lirgsmentioning
confidence: 99%
“…18. L CO /L TIR as a function of L TIR for various extragalactic sources: NGC 6240 (Meijerink et al 2013), NGC 1266 (Pellegrini et al 2013), M83 (Wu et al 2015b), Arp 220 (Rangwala et al 2011), M82 (Kamenetzky et al 2012), Mrk 231 (van der Werf et al 2010, and IC 342 (Rigopoulou et al 2013). The sources are color coded based on the dominant heating mechanism: UV photons (red), X-rays (purple), and mechanical heating (blue).…”
Section: Origin Of Shocksmentioning
confidence: 99%